2003
DOI: 10.1258/000456303766477011
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of adenosine deaminase in tuberculous pleural effusion: a meta-analysis

Abstract: Background Many studies have investigated the usefulness of adenosine deaminase activity (ADA) in pleural fluid for the early diagnosis of tuberculous pleurisy. To summarize the diagnostic characteristics of ADA we undertook a metaanalysis using a summary receiver operating characteristic (SROC) curve method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 35 publications
(13 reference statements)
3
78
2
3
Order By: Relevance
“…Paired data from two studies did suggest that in a direct comparison the NAAT tests were more accurate than ADA, but this was predominantly influenced by a single, small study using an inadequate reference standard, which produced very low sensitivity and specificity estimates for ADA. 212 Two previous meta-analyses assessing ADA for detection of pleural infection also found ADA to perform well (Q-points of 93% from 31 studies 86 and 92.2% from 40 studies 189 ). Both reviews included case-control studies and per specimen data.…”
Section: Discussion: Test Accuracy In Pleural Tb Infectionmentioning
confidence: 88%
“…Paired data from two studies did suggest that in a direct comparison the NAAT tests were more accurate than ADA, but this was predominantly influenced by a single, small study using an inadequate reference standard, which produced very low sensitivity and specificity estimates for ADA. 212 Two previous meta-analyses assessing ADA for detection of pleural infection also found ADA to perform well (Q-points of 93% from 31 studies 86 and 92.2% from 40 studies 189 ). Both reviews included case-control studies and per specimen data.…”
Section: Discussion: Test Accuracy In Pleural Tb Infectionmentioning
confidence: 88%
“…This cutoff value shows high efficiency in the classification of lymphocytic effusions (sensitivity: 87 to 100% and specificity: 81 to 97%). [19][20][21][22][23][24][25] Despite the high diagnostic sensitivity of ADA, its specificity is influenced by other clinical conditions and by the regional prevalence of tuberculosis. 26,27 In the present study, 13 (9%) patients with cancer presented an ADA activity higher than 40 U/L.…”
Section: Discussionmentioning
confidence: 99%
“…A total of ten eligible studies (in English) were identified [12][13][14][15][16][17][18][19][20][21]. To this list, we added two meta-analyses published as abstracts [22,23].…”
Section: For Reprint Orders Please Contact Reprints@future-drugscommentioning
confidence: 99%
“…To this list, we added two meta-analyses published as abstracts [22,23]. TABLE 2 lists the results of all 12 meta-analyses [12][13][14][15][16][17][18][19][20][21][22][23]. All were published within the past 5 years, and included a total of 513 diagnostic trials (with some overlap across meta-analyses).…”
Section: For Reprint Orders Please Contact Reprints@future-drugscommentioning
confidence: 99%
See 1 more Smart Citation